Measurement of exclusive rho(770)(0) photoproduction in ultraperipheral pPb collisions at root s(NN)=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer New York LLC, 2019)
Exclusive ρ(770) 0 photoproduction is measured for the first time in ultraperipheral pPb collisions at √s NN = 5.02 TeV with the CMS detector. The cross section σ (γp → ρ(770) 0 p) is 11.0 ± 1.4 (stat) ± 1.0 (syst) μb at Wγ p = 92.6 GeV for photon–proton centre-of-mass energies Wγ p between 29 and 213 GeV. The differential cross section dσ/d|t| is measured in the interval 0.025 < |t| < 1 GeV2 as a function of Wγ p , where t is the squared four-momentum transfer at the proton vertex. The results are compared with previous measurements and theoretical predictions. The measured cross section σ (γp → ρ(770) 0 p) has a power-law dependence on the photon–proton centre-of-mass, consistent with electron–proton collision measurements performed at HERA. The Wγ p dependence of the exponential slope of the differential cross section dσ/d|t| is also measured